Implementing the GIS technique for RFI mapping for radio astronomy in Malaysia - Roslan, Umar; Abidin, Z.Z.; Ibrahim, Z.A. (2011)
Geographical Information System (GIS) can be used as a powerful tool in mapping large areas with varying Radio Frequency Interference (RFI) profiles. In this paper, we report the initial testing of the usage of this system in order to identify the areas with the lowest RFI. Among the important parameters used to develop the database for our GIS are information on population density, location and power of telecommunication transmitters, annual rainfall level, main road network and land contour. We will also se information gathered from on-site RFI level measurements on selected prime areas generated by the GIS. The aim is to find the best site for the purpose of building a radio astronomical dish system in Malaysia, the first of its kind.